2012
DOI: 10.1155/2012/741741
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Induced CD8+ T-Cell Dysfunction in Lung Cancer Patients

Abstract: Lung cancer is the leading cause of cancer deaths worldwide and one of the most common types of cancers. The limited success of chemotherapy and radiotherapy regimes have highlighted the need to develop new therapies like antitumor immunotherapy. CD8+ T-cells represent a major arm of the cell-mediated anti-tumor response and a promising target for developing T-cell-based immunotherapies against lung cancer. Lung tumors, however, have been considered to possess poor immunogenicity; even so, lung tumor-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 110 publications
(146 reference statements)
3
52
1
5
Order By: Relevance
“…Although it is difficult to provide proper proof of immunosurveillance in humans (21), a large body of evidence supports the idea that developing cancers are not ignored by the immune system. Evidence for immunosurveillance of lung cancer can be found in patients with HIV infection who have an increased frequency of virally induced malignancies (22,23), and in immunosuppressed organ transplant recipients who have a higher risk of developing NSCLC (24). Further support of immunosurveillance in NSCLC can be found in studies that have demonstrated the ability of the immune system to spontaneously recognize tumor-associated antigens (TAAs) (25).…”
Section: Immunosurveillance Of Lung Cancer General Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is difficult to provide proper proof of immunosurveillance in humans (21), a large body of evidence supports the idea that developing cancers are not ignored by the immune system. Evidence for immunosurveillance of lung cancer can be found in patients with HIV infection who have an increased frequency of virally induced malignancies (22,23), and in immunosuppressed organ transplant recipients who have a higher risk of developing NSCLC (24). Further support of immunosurveillance in NSCLC can be found in studies that have demonstrated the ability of the immune system to spontaneously recognize tumor-associated antigens (TAAs) (25).…”
Section: Immunosurveillance Of Lung Cancer General Conceptmentioning
confidence: 99%
“…It has been demonstrated that many effector immune cells are anergic and have reduced functions in the lung tumor microenvironment (23,31). In addition, lung tumor cells may induce a loss or down-regulation of HLA class I molecules during tumor progression, modulating the susceptibility of tumor cells to lysis by cytotoxic CD8…”
Section: Tumor Intrinsic Factors With Immunosuppressive or Immunogenimentioning
confidence: 99%
“…This apparent discrepancy between the in vitro and in vivo functionality of CTLs in ACT is largely attributed to the presence of immunosuppressive barriers within the tumor microenvironment, which are co-opted by tumors to evade the host immune system (8)(9)(10)(11). Of these, TGF-β is a key cytokine during tumor pathogenesis secreted and upregulated by a wide variety of tumors, including melanoma and lung cancer (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…However, as our collective understanding of cancer immunology has evolved, more promising forms of immunotherapy have emerged. In particular, strategies targeting negative regulators (i.e., checkpoints) of the immune system have demonstrated significant antitumor activity across a range of solid tumors, including non‐small cell lung cancer (NSCLC)—a malignancy long considered poorly immunogenic . In recent years, checkpoint inhibitors targeting the programmed cell death protein‐1 (PD‐1)/programmed cell death ligand‐1 (PD‐L1) axis have shown significant antitumor activity in NSCLC .…”
Section: Introductionmentioning
confidence: 99%